نسق التجديد في الشعر الشعبي الجزائري ديوان (حب البيضا) للشاعر عبد السلام نجيب شعبان أنموذجا - ثابت, طارق (جامعة الوادي - University of Eloued, 2019)
ظهور القصيدة الشعبية الحديثة كان نتاجا لثورة فكرية وثقافية، سياسية واجتماعية وحتى اقتصادية، عجّلت بما يسمّى التجديد لدى شعراء الملحون وبخاصة لدى مجموعة من الشعراء، فارتبط الشعر عندهم بالخيال و الرمز ، ممّا جعله يختلف عمّا كان عليه سابقا. والخوف من التجديد عند شعراء الشعبي هو خوف من جمهور ألف العادي والجاهز ، ومن سُلطة وضعت الشعر الشعبي في خانة عناصر الهوية ، التي تتكئ عليها، و التي تراها صوتا لا يمكن أن يكون خارج سلطتها كما قال أحد الدارسين، فما هو مفهوم التجديد في الشعر الشعبي ؟ و ما هي مظاهره ؟ وكيف تجلّت هذه المظاهر عند أحد أبرز شعراء الملحون الشاعر عبد السلام نجيب شعبان في ديوانه حب البيضا؟. Abstract The emergence of the modern folk poem was the result of an intellectual and cultural revolution, political, social and even economic, which accelerated the so-called renewal of the poets of the people, especially among a group of poets, linked poetry to their imagination and symbol, which made it different from what it was before. The fear of regeneration among the poets of the popular is the fear of the audience accustomed to the ordinary and ready, and from the authority put popular poetry in the field of identity elements, which lean on them, which you see a voice that can not be outside its authority, as one of the scholars, what is the concept of renewal in poetry? What are its manifestations? And how these manifestations manifested when one of the most prominent poets of the popular poet Abdul Salam Najib Shaaban in his office love Albida?.
مقال
Keywords: الشعر الشعبي؛ التجديد؛ الشعر الملحون؛ عبد السلام شعبان؛ حب البيضاء.